A conceptual study on the use of space for domestic activities and productive activities in household-based businesses - Pindo Tutuko (Jurnal Penelitian, 2005)
The strength of tradition supports the stability of the elements from one generation to another. This shows that from one community group there is a tradition in which every element of the tradition will be passed down to the next generation. The house is not just a place to shelter, rest, and have a family, but it can also function to mobilize the residents' resources by looking at the opportunities that exist. In general, the concept of home and work includes social and cultural dimensions, namely as a house that is used as a place to live without other meaningful activities, and a production house, namely a house that is partly used for productive or economic activities. There is a use of space that should be mostly for residential needs (domestic) into activities for doing business (productive). Household Based Enterprises (UBR) in Kampung Sanan "Tempe' Malang, experienced a change in the pattern of occupancy which was influenced by the part of the house that was important to their business.